ANALISIS SISTEM PENYELENGGARAAN MAKANAN DAN HUBUNGAN DAYA TERIMA, ASUPAN MAKANAN TERHADAP STATUS GIZI LANSIA - Sandi Ayu Wijaya; Laras Sitoayu; Tiurma Heryawanti Pakpahan (Jurnal Sains Kesehatan, 2017)
Elderly in Indonesia who lived in urban areas, especially those living in institutions that were in malnutrition is 28.3% weight less, weight 6.7%, obesity 3.4% and ideal weight 42.4%. The purpose of this study was to analyze the system of food management, acceptance power, food intake against elderly nutritional status in social institution Tresna Werdha Budi Mulia 01 Cipayung. The type of research used in this research was Observational with Cross-Sectional approach. Population in this research was all elderly in Social House Tresna Werdha Budi Mulia 01 Cipayung. Sampling in this study was taken using Purposive Sampling method, with a total sample of 31 people. The data analysis was descriptive analysis, univariate and bivariate analysis using Chi-Square statistical test. The results showed that there was a relationship between food acceptance and nutritional status of the elderly and there was also a relationship between food intake with nutritional status of the elderly. Keywords:  elderly, food acceptance, food intake, food service management